Perancangan Sistem Booking Salon Berbasis Web pada Salon Ratih Langit - I Putu Eka Indrayana; Ni Made Satvika Iswari; I Nyoman Purnama (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The beauty service industry is experiencing digital transformation as consumer demand for convenience increases. Salon Ratih Langit, a beauty salon in Bali, still uses manual methods for booking and managing appointments, resulting in inefficiencies such as scheduling conflicts and disorganized transactions. This study aims to design a web-based booking system to streamline the reservation process and improve customer experience. Using the Software Development Life Cycle (SDLC) with a prototyping approach, the system was designed through iterative feedback from users. The system allows customers to register, choose services, schedule appointments, and make payments online, while providing admins with tools to manage bookings. The design includes UML diagrams, ERD, and interactive interfaces using Figma. Usability testing was conducted using the System Usability Scale (SUS), yielding a score of 73.33, which falls under the “Good” category. The system is expected to enhance efficiency and customer satisfaction while reducing human errors in booking processes.